Identification of rice varieties through chemical tests - JITENDRA KUMAR TIWARI,; N.K. RASTOGI,; PK. CHANDRAKAR,; A.K. SARAWGI,; S.B. VERULKAR, (Seed Research, 2026)
Variety identification has great significance from seed production, breeding as well as intellectual property rights point of view to ensure quality seed. Four varieties of rice were identified on the basis of seed colour (phenol, modified phenol and NaOH) and seedling response (GA, and 2, 4-D) to chemical tests. Though no individual chemical test was able to distinguish all the varieties, different chemical tests in conjunction were useful in identification of varieties. Karma Mahsuri exhibited negative response to phenol test and positive response to modified phenol test. However, three varieties namely, Danteshwari, Samleshwari and Mahamaya recorded positive response to both phenol and modified phenol test. Varieties Karma Mahsuri, Samleshwari and Mahamaya showed yellow colour reaction with NaOH test while, Danteshwari showed yellowish brown reaction. The effect of GA, and 2, 4-D on coleoptile growth of seedling was found to be variable among varieties studied.